Providing a Behavioral Educational Model for Socially Vulnerable Groups - Masoum Beigi, Mohammadreza; Banisi, Parinaz; Jahed, Hoseinali (Management Strategies and Engineering Sciences, 2025)
The objective of the present study was to propose a behavioral educational model for socially vulnerable groups. The research was applied in terms of its objective and employed a mixed-method exploratory design. In the qualitative phase, thematic analysis was used, while the quantitative phase employed a descriptive-survey approach. The statistical population in the qualitative phase included academic experts and experienced officials from universities in Tehran, who were selected using non-probability purposive sampling. In the quantitative phase, the statistical population consisted of all stakeholders involved with child labor in Tehran Municipality, including managers and deputies, who were selected through structural equation modeling. Stratified random sampling was used in this phase. Data collection tools included semi-structured interviews in the qualitative phase and a researcher-made questionnaire in the quantitative phase. To assess internal validity in the qualitative phase and external validity of the researcher-made questionnaire based on the model components, relevant metrics were used. In the qualitative phase, the credibility criterion was applied, and reliability was examined through detailed documentation of the research process and intra- and inter-researcher alignment. Additionally, in the quantitative phase, validity was assessed using content and construct validity, while reliability was measured using Cronbach's alpha and composite reliability coefficients. Data analysis in the qualitative phase involved thematic analysis using Maxqda-V2018 software, whereas the quantitative phase applied descriptive and inferential statistics using SPSS-v23, SmartPLS-v3, Lisrel V8.8, and ExpertChoice-V11 software. The findings revealed that the dimensions of the behavioral educational model for socially vulnerable groups included educational (curricula, teaching methods, educational equipment and resources, educational evaluation, teacher professional development, extracurricular activities), psychological (psychological support, psychological empowerment, psychological care, emotional support, family support), social (social support, opportunities for social participation, social awareness, enhancement of social skills, promotion of social solidarity, social networking), economic (job skills, entrepreneurship, local economic development, financial management training, economic empowerment), and cultural (preservation of cultural identity, cultural education, cultural communication, artistic development, protection of cultural heritage, cultural promotion) aspects. The results of this study not only contribute to improving the behavior of socially vulnerable groups but also serve as an effective tool for enhancing the quality of behavioral education for child laborers.